PENGARUH JENIS MEDIA TANAM DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH KERITING (Capssicum annum L.) - Rika Wiji Lestari (grafting, 2021)
The study aims to determine the interaction, concentration between planting media and POC queen biogen and find out the right media for the growth and yield of curly red chili plants. The study design used a randomized design of a group of factorial patterns, factor I type of planting media namely M1: Soil, M2: soil and husks 3: 2, M3: soil and husk charcoal 3: 2, factor II concentration of liquid organic fertilizer (POC) Ratu Biogen namely P1: Without POC, P2: 2 ml / l, P3 : 4ml / l, P4 : 6 ml / l. The results of the fingerprints showed that there was a real interaction of the treatment of the type of planting medium (M) and the concentration of POC queen biogen (P) on plant height, stem diameter, number of leaves, number of fruits. The best treatment is found in the type of soil planting media and 3:2 husks and 6ml/l POC Ratu Biogen (M2P4).